Shaping digitalization among German tourism service providers: Processes and implications - Hannes Thees; Elina Störmann; Franziska Thiele; Natalie Olbrich (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: This study aimed to assess the external factors influencing ICT usage at UNESCO World Heritage Sites (WHS), focusing on This study addresses the digital transformation in tourism, accelerated due to the COVID-19 pandemic. By linking the front- and backstage activities, a model of the tourism value system is sketched with the aim to assist the shift toward digital value creation in the case of the German tourism sector by asking, What are the challenges for the digital transformation of tourism service providers, and how can it be promoted along with the tourism value system?